INFLUENCIA DE LOS SISTEMAS MULTIMEDIA EN EL PROCESO DE ENSEÑANZA APRENDIZAJE DE LOS ESTUDIANTES DE PRIMERO DE BACHILLERATO DE LA UNIDAD EDUCATIVA EUGENIO ESPEJO EN EL PERIODO LECTIVO 2023 -2024. - MONTOYA RIVERA JAVIER ANTONIO (2024)
The theme of my project is called the influence of multimedia systems on the teaching-learning process of first-year high school students of the Eugenio Espejo educational unit and aims to analyze how interactive teaching-learning affects the cognitive development of students. Technology is currently very important in education, emphasizing the fundamental role of multimedia systems in improving the learning experience. Multimedia content transmits information with technological resources such as images, graphs, videos or diagrams that help illustrate concepts that would be easy for students to understand and learn. Animations and simulations help to visualize abstract or difficult to imagine processes, in addition you can access multimedia content that are platforms, of which we have: YouTube, Khan Academy among others, these platforms offer thousands of educational videos such as online cursors and tutorials that address a variety of topics. The project is a research methodology that consists of collecting, analyzing, and integrating both quantitative and qualitative research. The quantitative includes closed information that is used to measure attitudes as a scoring scale and the qualitative measures open information that the researcher collects through interviews. Finally, in an increasingly digitized society, it is very important for students to develop skills to use and understand technology.